Surveying the IT Infrastructure Challenges in Afghanistan - Frugh, Qurban Ali; Naseri, Mohammad Fahim (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
The rapid advancement of technology has brought significant transformations across various sectors globally, including in Afghanistan. However, the country's Information Technology (IT) infrastructure remains underdeveloped, particularly in key areas such as health, e-commerce, telecommunications, e-governance, academic research, education, and culture. This research paper analyzes the challenges faced by the IT infrastructure in Afghanistan. In January 2024, there were 7.88 million internet users in Afghanistan, representing 18.4% of the total population. The aim of this study is to identify the current challenges of IT infrastructure and assess their impact on users' access to the digital world. A systematic review of scientific, research, and administrative documents was conducted to gather data. Quantitative analysis of these documents reveals that only a small segment of the population has access to technology, and their usage is primarily limited to social media and virtual spaces. The study found that Afghanistan's IT infrastructure is weak and insufficient to support the development of e-governance, e-commerce, banking, healthcare, and educational systems. Several factors contribute to these challenges, including slow internet speeds, high costs, and limited access to technology compared to neighboring countries. Based on these findings, the paper proposes potential solutions to improve the IT infrastructure in Afghanistan, with a focus on addressing the identified weaknesses and ensuring broader access to digital services.